Mingle Game Activities in Task-Based Language Teaching (TBLT) : Essential Tool to Improve Students Speaking Skills in Thai Primary School Students - P.A, Novia Lestari; Amran, Ali; Syahputri, Diani (Journal of English Language and Education, 2025)
Speaking skill is a crucial component of English language learning, especially for EFL students in primary schools, where opportunities to practice real-life communication are limited. This gap between theoretical teaching strategies and classroom practice highlights the need for more interactive and learner-centered approaches. This study explores how Mingle Game Activities within a Task-Based Language Teaching (TBLT) framework can improve students’ speaking skills. A quasi-experimental method was employed, using a pretest-posttest design with control and experimental groups. Speaking tests were used to assess students’ performance, and the data were analyzed using paired and independent sample t-tests. The results revealed a significant improvement in the experimental group’s speaking skills, particularly in vocabulary usage, fluency, and confidence. These findings suggest that Mingle Game Activities are a promising strategy to foster student engagement and enhance speaking ability in interactive English learning environments within EFL classrooms.